The Rue Mosnier with Flags - Édouard Manet (Wikimedia Commons, 1878)
Notice iconographique issue de Wikimedia Commons. Titre: The Rue Mosnier with Flags. To commemorate the recent Exposition Universelle, itself a celebration of luxury and prosperity, the French government declared June 30, 1878, a national holiday. The holiday, called the Fête de la Paix (Celebration of Peace), also marked France's recovery from the disastrous Franco-Prussian War of 1870-1871 and the bloody, divisive Paris Commune that followed. From his second-floor window, Édouard Manet captured the holiday afternoon with his most precise, staccato brushwork in a patriotic harmony of the reds, whites, and blues of the French flag that waves from the new buildings' windows. The urban street was a principal subject of Impressionist and Modernist painting | many artists aimed to show not only the transformation and growth of the Industrial Age but how it also affected society. Manet's eyes saw both elegant passengers in hansom cabs and, in the foreground, a worker carrying a ladder. The hunched amputee on crutches, perhaps a war veteran or beggar, passes by fenced-in debris left from the construction of a new train track. Manet's sensitivity to the associated costs and sacrifices tempered his optimistic view of national pride and newfound prosperity.
Licence Public domain via Wikimedia Commons
Keywords: œuvre d'art; tableau; sculpture; statue; wikimedia commons